Inquiry-based science activities in grades 6-12 : meeting the NGSS - Brown, Patrick, 1978-; Concannon, James (Routledge, 2018)
"This new book shows middle and high school science teachers how to use evidence-based inquiry to help students achieve deeper conceptual understanding. Drawing on a wealth of research, authors Pat Brown and Jim Concannon demonstrate how direct, hands-on experience in the science classroom can enable your students to become more self-reliant learners. They also provide a plethora of model lessons aligned with the Next Generation Science Standards (NGSS) and offer advice on how to create your own lesson plans and activities to satisfy the demands of your curriculum. With the resources in this book, you and your students will be able to ditch the textbook and embark upon an exciting and rewarding journey to scientific discovery.?"- Resumé vydavatel